Sistemas de escoamento superficial como alternativa de pós-tratamento de esgotos tendo a palma forrageira (Opuntia fícus indica L. Mill) como vegetação suporte - Silva Filho, Pedro Alves da (2014)
The research aimed to evaluate the performance of sewage treatment plants septic-type anaerobic filters located in the state of Rio Grande do Norte and its study of post-treatment technique runoff aimed at removing nutrients (N and P) and pathogens, tailoring the physico-chemical and microbiological standards required for the reuse and considering legislation to launch in the receptor fluid, evaluating such studies in the temporal / spatial having spineless cactus (Opuntia ficus-indica (L.) Mill) as plant species grown on the slopes of runoff. For this work we used the cactus pear (Opuntia ficus indica L.Mill) because it has great adaptation to drought and strong native to northeastern Brazil, as well as the uniqueness in the cultivation of aquatic vegetation using domestic sewage. The survey was conducted in Santa Maria, located in Wastewater Treatment Plant of in Santa Maria, Rio Grande do Norte. Ramps were built three runoff with different slopes, 2%, 4% and 8% with 30 meters long and 10 meters further on ramp 8% incline. The liquid was applied to the ramps sewage in nature, with primary treatment and secondary treatment, from septic tanks and anaerobic filters. Application rates of sewage tested were 0.20 m³ / hm, 0.30 m³ / hm and 0.4 m³ / hm. We evaluated the ability of the system to remove nutrients, nitrogen and phosphorus as well as organic matter. With the realization of quantitative analysis was possible to determine which slope allowed greater removal and which operating flow. Of the three steps, the rate of 0.40 m³ / hm and inclination of 8% showed the best efficiency, being 93.55% and the concentration of 25.67 mg / L for BOD, 56.10% and concentration of 17.65 mg / L for N-total, 25.94% and the concentration of 5.98 mg / L for P -total, 4 logs and 1.89 x103 NMP/100mL concentration of coliforms and 22.20% to 534.29 final concentration μS / cm electrical conductivity. The influent wastewater to the WTP parameters of BOD, N-total, P-total coliforms Thermotolerant and Electrical Conductivity for the 3rd stage were 398.12 mg / L, 40.22 mg / L, 8.08 mg / L; 2.81 x107NMP / 100mL and 686.75 mS / cm respectively. A septic tank and anaerobic filter, and the post-treatment system had values within the range mentioned in the literature were 34.68% and the final concentration of 260.02 mg / L, 78.61% and the final concentration of 85.14 mg / L to 93.55% and the final concentration of 25.67 mg / L respectively, for the best rate of application was 0.40 m³ / um and a gradient of 8%. In all aspects examined, the system has improved the quality of the final effluent, showing up as an alternative, with simple, inexpensive technique compatible with the economic reality of the Brazilian Northeast, although the rate of 0.20 m³ / hm and 0.30 m³ / hm showed a slightly lower efficiency of 0.40 m³ / um, they can not be discarded, since the values found are partially within the ranges quoted in the literature.